2017
DOI: 10.4236/ojn.2017.77064
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Perception of Missed Care: Focus Group Results

Abstract: Background: With the inflation of economic constraints on health care and demand to increase care quality, there is an increasing need to develop a clear understanding of what actions by health professionals are perceived as threatening quality care. Objective: To explore graduate nursing and pastoral care student's perceptions of missed care in Norway. Research design: A qualitative study was employed with the formation of six focus groups. Data was analyzed via a thematic content of the discussions. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…All of them were final year students of the bachelor study program. An interview guide was developed based on the literature review (12,13). The interviews lasted between 18 to 26 minutes, were recorded using a voice recorder, and transcribed verbatim.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them were final year students of the bachelor study program. An interview guide was developed based on the literature review (12,13). The interviews lasted between 18 to 26 minutes, were recorded using a voice recorder, and transcribed verbatim.…”
Section: Methodsmentioning
confidence: 99%
“…Nursing students directly or indirectly contribute to the prevalence of rationed nursing care (11). However, nursing students´ experience with this phenomenon have been described only in three qualitative studies (12)(13)(14). These studies have not reported the nursing students´ perspectives on their experiences with preventive strategies and the importance of these strategies for clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…They may have developed a deeper understanding of nursing concepts, including teamwork dynamics, leadership, and patient care management. Their advanced knowledge equips them to provide more nuanced insights into the relationship between UNC and teamwork (Kalfoss, 2017;Palese et al, 2023). By incorporating their voices into UNC discussions, both nursing education and practice can evolve to better address this complex issue and promote comprehensive, patient-centered care delivery.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Scandinavian study noted that as students, nurses do indeed understand the legacy of missed care on their clinical practice and that there were multiple barriers within the clinical environment, which lead to care omission. These include poor communication skills, increased workloads, ineffective collegial relationships, unproductive leadership and emotional strain including powerlessness (Kalfoss, 2017).…”
Section: Introductionmentioning
confidence: 99%